318. PET/CT image alignment: Methodology for assessment using a dedicated phantom. (December 2018) - Spadavecchia, C.; De Ponti, E.; Morzenti, S.; Crespi, A.
Abstract : Purpose: the alignment of transmission and emission images is a crucial requirement in nuclear medicine hybrid scanners (PET/CT and SPECT/CT). EANM and Italian (AIFM-AIMN) guidelines prescribe to perform the alignment test by using specific manufacturer phantoms combined with closed source analysis software packages supplied by the vendor. The purpose of this work was to propose a full independent tool for evaluating CT and PET images alignment by scanning a commercially available phantom. Methods: PET/CT data were acquired on a Discovery-IQ PET/CT system (GE Healthcare, Milwaukee, USA) using a dedicated phantom (PET/CT Phantom, Data Spectrum Corporation). A Matlab code was written to perform image analysis. To evaluate translations, 5 coplanar spheres filled with 18F-FDG radioactive solution were considered through these steps: segmentation of the spheres using a region growing algorithm, calculation of the centre of mass for each sphere and comparison of its coordinates in PET and CT set of images. Rotations were assessed by considering the positioning of 3 aluminium rods filled with radioactive solution in PET and CT: the angles shown in figure were calculated in sagittal, coronal and axial views. A series of nominal translations (3–5–8–10 mm in the three spatial directions) and rotations (swivel, tilt and roll, 3.2° up to 6.8°) were simulated to validate the method. Results: the sensibility of the method turned out to be less than 1 mm for translations and between 1.0° and 1.7° for rotations. The reproducibility (coefficient of variation over 5 identical acquisitions) was less than 1% both for translations and for rotations. Linearity considered the detected translation/rotation as a function of the nominal one: the angular coefficient for the linear regression ranged from 0.87 (Y-axis translation) to 1.35 (tilt rotation). Conclusions: the method proposed represents an alternative to the use of vendor specific phantoms and software analysis, providing a general validity across each type of scanner.